Upaya Meningkatkan Kemandirian Belajar Prakarya dan Kewirausahaan dengan Metode Pemberian Tugas ( Resitasi ) di Kelas XIIK MAN Wates I Kabupaten Kulon Progo - Sihono Setyo Budi (Universitas Alma Ata, 2018)
This study aims to determine whether the method of giving the task (recitation) can improve the independence of learning in the class X IIK MAN WATES.The subject of this study is students of MAN Wates I Kulon Progo class X IIK as many as 30 students. The data is obtained by using observation sheets and independence test scale, the data analysis using quantitative and qualitative. From the analysis is found that giving task (recitation) method can improve the independence of learning. There is a significant increase between cycle I and cycle II. The average score of self-learning test in the first cycle of 7.4 and on the second cycle test of 7.9, the student activity in doing the Prakarya Dan Kewirausahaan is also increase , 71,4% in cycle I and 80,7% in cycle II.Keywords: Method of Recitation, Learning Independence